Midwifery Care for Postpartum Mothers With After Pain Discomfort in Maternity Homes and Clinics: Asuhan Kebidanan pada Ibu Nifas Dengan Ketidaknyamanan After Pain di Rumah Bersalin dan Klinik - Hafifa, Hafifa; Hanum, Sri Mukhodim Faridah; Rosyidah, Rafhani (Universitas Muhammadiyah Sidoarjo, 2020)
The postpartum period is an important period for health workers to monitor the mother's condition. The coverage of postpartum mothers' visits in 2016 was 71.54%. target coverage of postpartum mother visits in 2017 with the aim of transferring knowledge and complete postpartum visits. This type of method uses a descriptive method. whose main purpose is to make an objective picture of a situation.